Cytoskeleton-associated protein 2 (CKAP2) is regulated by vascular endothelial growth factor and p53 in retinal capillary endothelial cells under high-glucose conditions. (15th September 2021) - Chen, Xiangting; Xie, Jie; Cui, Ying; Zhang, Liang; Yu, Honghua; Chen, Jing; He, Mengxia; Liu, Shuangxin; Huang, Tian; Chen, Lu; Fang, Dong; Zhu, Ying; et al.
Abstract: Purpose: We previously found the mutation frequency of cytoskeleton-associated protein 2 (CKAP2) was significantly increased in proliferative diabetic retinopathy (PDR) patients through whole exome sequencing. The present study was conducted to explore the expression and possible mechanism of CKAP2 in PDR patients and human retinal capillary endothelial cells (HRCECs) under high-glucose (HG) conditions. Methods: Expression of CKAP2 and p53 in the vitreous fluid and fibrovascular membrane (FVM) of PDR patients and HRCECs under HG conditions was observed. Cell proliferation, migration and tubule formation were assessed. Ranibizumab and siRNA transfection were used in the inhibition assay. Results: CKAP2 and p53 were significantly increased in the ocular tissues of PDR patients. HG combined with VEGF treatment significantly up-regulated expression of CKAP2 and p53 in HRCECs. Inhibition of CKAP2 attenuated the abilities of cell proliferation, migration and tube formation under HG conditions. Blocking VEGF or p53 significantly decreased CKAP2 expression, whereas inhibition of CKAP2 failed to alter the level of VEGF or p53. Conclusions: CKAP2 is involved in the pathogenesis of PDR and regulated by VEGF and p53 under HG conditions. Highlights: CKAP2 is significantly increased in ocular tissues from PDR patients. CKAP2 changes cell biological behavior under high-glucose conditions. CKAP2 is regulated by VEGF and p53 under high-glucose conditions.